Induki Mutasi dengan Sinar UV-C dan Seleksi In Vitro Kalus Kedelai yang Toleran Kekeringan - Allatifa, Mumthaza; Gustian; Sutoyo (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2025)
Soybean (Glycine max. L) is a strategic commodity that plays a major role in providing nutritious food. One effort to increase soybean production is through the use of superior varieties. Dega-1 is a soybean variety that is very sensitive to drought so that it is necessary to develop soybeans cultivated in dry land which can be attempted through mutation breeding. The purpose of this study was to determine the duration of ultraviolet C light irradiation that can produce mutants and to obtain putative drought-tolerant mutants through ultraviolet C light mutation induction and in vitro selection (PEG 25%). This study was conducted from April to July 2024 at the Tissue Culture Laboratory, Faculty of Agriculture, Andalas University. This study was arranged in a Randomized Block Design with treatment duration of UV C light irradiation λ 254 nm with 10 treatment levels including no radiation, 15 minutes, 30 minutes, 45 minutes, 60 minutes, 75 minutes, 90 minutes, 105 minutes, 120 minutes, and 135 minutes. Each treatment consisted of 5 groups. The observation data were analyzed using simple statistical analysis using the mean and standard deviation calculations. The results showed that the highest percentage of putative drought-tolerant soybean mutants (PEG 6000 25%) was produced by 45 minutes of UV C irradiation, namely 3.33%. These mutants emerged from blackish-brown callus and developed into yellow callus and also regenerated into somatic embryos.